Cognitive mediation of putting: Use of a think-aloud measure and implications for studies of golf-putting in the laboratory - Arsal, G.; Eccles, D. W.; Ericsson, K. A. (Psychology of Sport and Exercise, 2016)
Objectives: Whereas accounts of skilled performance based on automaticity (Beilock & Carr, 2001; Fitts & Posner, 1967) emphasize reduced cognitive involvement in advanced skill, other accounts propose that skilled performance relies on increased cognitive control (Ericsson & Kintsch, 1995). The objective of this study was to test predictions differentiating the automaticity and cognitive control accounts by assessing thinking during golf putting. Design: The cognitive processes of less-skilled and more-skilled golfers were examined during putting using concurrent, think-aloud verbal reports. The design included putting conditions that differed in complexity and thus the need to adapt the putt to the particular conditions. Method: Putting complexity was manipulated via changes to putt length and perceived stress during putting. Putts were executed from two starting locations (i.e., the same starting location as the previous putt or a new starting location). Results: The analysis showed that, during putting: more thoughts were verbalized overall by more-skilled golfers than less-skilled golfers; both groups verbalized more thoughts overall during higher-complexity putts (i.e., longer distance putts, and putts under higher stress when executed from a new starting location) than lower-complexity putts; and the two groups did not differ significantly in the number of thoughts related to motor mechanics. Conclusions: The results of this study provide support for a cognitive control account of skilled performance and suggest that the path to skilled performance involves the acquisition of more refined higher-level cognitive representations mediating planning and analysis.